Pharmacist Experience in Discovering Forged Prescriptions in Pharmacies In the Special Region of Yogyakarta - Muvita Rina Wati; Istiqomah Dwi Oktaviani; Ahmad Fahmy bin Yahya; Bondan Ardiningtyas; Anna Wahyuni Widayati (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Pharmacies were a source of narcotics and other addictive agents by 2.1% of respondents to a survey conducted by BNN and LIPI in 2019. One way for drug abusers to obtain drugs is to use forged prescriptions. Therefore, the accuracy of pharmacists in prescription's screening is needed to reduce the prevalence of drug abuse. Research on prescription counterfeiting has been carried out in various developed countries, but similar research has never been conducted in Indonesia. This study aims to determine the patterns, characteristics, and experience of pharmacists in the Special Region of Yogyakarta (DIY) pharmacy in responding to counterfeit prescription findings. This research is an observational study with a survey method using a research instrument in the form of a questionnaire. A total of 152 pharmacists in DIY were involved as respondents and filled out questionnaires both online using the Google Form and offline from November to December 2019. The research data were analyzed descriptively. Based on the results of the study, most of respondents 85%) had encountered counterfeit prescriptions. They were identified by the following characteristics, including the doctor's writings that were not the same as usual (60%), the amount of medicine was irrational/added with 'iter' (59%), absence of doctor’s registration number (41%), stamp (44%), and doctor's signature (32%). The most common drug classes written on fake prescriptions include psychotropics, followed by other drug classes, namely drugs that are often abuse, narcotics, antibiotics, and other ethical drugs (misoprostol and levonogestrel). In identifying counterfeit prescriptions, pharmacists need a guideline, training, and coaching. In addition, clear supervision and reporting channels are needed so that prescription counterfeiting can be reported and seriously followed up by involving Indonesian Pharmacist Association (IAI), Health Office (Dinas Kesehatan), and Indonesia Food and Drug Administration (POM).